The New Security Individual, Community and Cultural Experiences - Forbes-Mewett, Helen (Crime Prevention and Security Management, 2018)
The New Security places the concept of 'security' under the spotlight to analyse its meaning in an original and contemporary context. In so doing, Forbes-Mewett revisits the notion from the perspectives of individuals and communities to understand what security means in our culturally diverse, contemporary society. Chapters highlight the extent of the shift of traditional uses of the term from the established perspective of international relations to a more commonly used concept which now broadly relates to many aspects of peoples' everyday experiences. Based on empirical studies of security in relation to housing, employment, food, personal security and campus settings in times of perceived heightened risk, this book presents new and different ways of thinking about security to demonstrate how we need to expand the dialogue surrounding the concept. Drawing on empirical research to describe, analyse and reposition the concept of security to have meaning in diverse everyday contexts, this methodological and insightful text will be of particular interest to scholars and students of criminological theory, security studies and sociology. .